Use Of Picture and Picture to Improve English Vocabulary Mastery In Students IX-C Mentally Impaired - Mayani, Sari (BAHTRA: Pendidikan Bahasa dan Sastra, 2022)
This study aims to describe the use  of Picture and Picture  to improve the ability to master English vocabulary of students with intellectual disabilities grade IX-C SLB Negeri 1 West Lombok for the 2021/2022 academic year. In data collection researchers use observation, test and documentation techniques. The data were analyzed in a qualitative descriptive manner. This research was conducted in 2 cycles starting with a preliminary study. During the study, researchers found that in the pre-cycle, the level of students' vocabulary mastery ability was still low, namely 55.8% in the range of 40% - 55%. In the first cycle after students were given action with the use of  Picture and Picture,  the student's ability level increased to 61.5% and entered the medium criteria (56%-75%). In cycle II after students were given actions based on observations in cycle I, students' vocabulary mastery ability increased to 78.3%  so that it was included in the high criteria (76%-100%). From the results of the study, it can be concluded that the use of  Picture and Picture can increase student learning activities and increase vocabulary mastery